Effect Of Compensation and Job Satisfaction On Employee Performance At The Southwest Papua Pupr Officeprovince - Dominggus Djitmau; Andi Irwan; Wa Ode Likewati; Cakra Zaitun (International Journal of Management and Business Economics, 2026)
This study aims to examine the influence of compensation and job satisfaction on employee performance at the Public Works and Public Housing (PUPR) Office of Southwest Papua Province. A quantitative approach with a survey method wa employed, involving 40 employees as the research sample. Data were collected through questionnaires and analyzed using validity and reliability tests, multiple linear regression, t-test, F-test, and the coefficient of determination with SPSS. The results indicate that compensation has a positive and significant effect on employee performance (Sig. = 0.040), while job satisfaction has a positive and highly significant effect on employee performance (Sig. = 0.000). Furthermore, compensation and job satisfaction simultaneously have a significant effect on employee performance. These findings suggest that providing fair compensation and enhancing job satisfaction can improve employee performance at the PUPR Office of Southwest Papua Province.